2016
DOI: 10.4028/www.scientific.net/amr.1138.25
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Noxious Emissions of the Welding Process “Cold Metal Transfer (CMT)”

Abstract: For the examination of noxious emissions, cladding tests were performed according to EN ISO 6847. The filler materials were 1.2 mm diameter wire-electrodes, made of tin bronze, aluminium bronze, austenitic stainless steel, duplex stainless steel and nickel alloy.The low-energy metal transfer welding process, named CMT (cold metal transfer) was examined, on the welding source type Trans Puls Synergic 2700 CMT, of 270 A, produced by the company Fronius, Austria. For sampling welding smoke particles, an Apex type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Victor et al 6 have reported that the concentration of emission gas is comparatively very low during the CMT welding process; also, they have concluded that there is no health risk for the welders. Popović et al 7 have compared two-filler materials such as metal-cored wire and self-shielded wire welded to micro-alloyed steel.…”
Section: Introductionmentioning
confidence: 99%
“…Victor et al 6 have reported that the concentration of emission gas is comparatively very low during the CMT welding process; also, they have concluded that there is no health risk for the welders. Popović et al 7 have compared two-filler materials such as metal-cored wire and self-shielded wire welded to micro-alloyed steel.…”
Section: Introductionmentioning
confidence: 99%